Research Trends in The Utilization of E-Modules in Science Learning: A Systematic Literature Review - Fahmi Anhar Muladi; Maria Paristiowati; Cecep Kustandi; Imam Fitri Rahmadi; Arcita Rizara (Postgraduate, University of Mataram, 2026)
This study aims to systematically map research trends in the utilization of e-modules in science learning from 2020 to 2024. This study employed a Systematic Literature Review (SLR) approach following PRISMA guidelines to ensure a transparent and systematic selection process. Data were collected from the Scopus database, resulting in 261 identified articles, of which 20 empirical studies were selected through identification, screening, eligibility, and inclusion stages. The results show that the dominant research focus is development based on learning models (75.00%), with Problem-Based Learning as the most frequently used model (35.00%). In terms of learning outcomes, higher-order thinking skills (60.00%) and critical thinking skills (40.00%) are the most widely examined variables, while affective aspects remain underexplored. Technology integration is dominated by interactive multimedia (40.00%) and Android-based platforms (20.00%). However, the findings also reveal several gaps, including limited attention to affective outcomes, lack of methodological rigor, and insufficient consideration of contextual factors such as teacher readiness and digital equity. These findings highlight the need for more comprehensive, rigorous, and context-sensitive research to support sustainable digital learning in science education.